Three-year follow-up and patient-reported outcomes from CheckMate 078: Nivolumab versus docetaxel in a predominantly Chinese patient population with previously treated advanced non-small cell lung cancer. (March 2022) - Chang, Jianhua; Wu, Yi-Long; Lu, Shun; Wang, Jie; Mok, Tony; Zhang, Li; Feng, Jifeng; Wu, Lin; Tu, Hai-Yan; Zhang, Yiping; Luft, Alexander; Zhou, Jian-ying; et al.
Highlights: Continued benefit at 3 years with nivolumab vs chemo in Asian patients with aNSCLC. Nivolumab showed improvements in disease-related symptoms and overall health status. Findings support long-term use of 2L nivolumab in Asian patients with aNSCLC. Abstract: Objectives: In the phase 3 CheckMate 078 study, nivolumab prolonged overall survival (OS) and showed a favorable safety profile versus docetaxel in a predominantly Chinese patient population with previously treated advanced non-small cell lung cancer (aNSCLC). However, long-term efficacy, safety, and health-related quality of life findings with second-line nivolumab are very limited in Asian patients with previously treated aNSCLC. Here, we report updated clinical data and patient-reported outcomes (PROs) from the phase 3 CheckMate 078 trial with a 3-year minimum follow-up. Materials and methods: Patients with aNSCLC and disease progression after platinum-doublet chemotherapy were randomized 2:1 to nivolumab (3 mg/kg every 2 weeks) or docetaxel (75 mg/m 2 every 3 weeks) until progression or unacceptable toxicity. The primary endpoint was OS; secondary endpoints included objective response rate, progression-free survival, safety, and disease-related symptom deterioration assessed using the Lung Cancer Symptom Scale (LCSS) by Week 12. Additional PRO assessments were exploratory endpoints. Results: At ≥ 37.3 months follow-up, 3-year OS rates were 19% with nivolumab and 12% with docetaxel; 30% and 0% of responders remained in response for ≥ 3 years, respectively. Incidence of treatment-related adverse events occurring after 2 years was lower than during the first 2 years. No new treatment-related deaths were reported. By Week 12 of treatment, rates of disease-related symptom deterioration were 32% with nivolumab and 47% with docetaxel. Completion rates for PRO questionnaires were ≥ 80% in both arms. Clinically meaningful and sustained improvements in LCSS Average Symptom Burden Index scores and delayed time to first symptom deterioration were observed with nivolumab against docetaxel. Conclusions: At 3 years, nivolumab continued to demonstrate survival benefit versus docetaxel, exhibiting improvements in disease-related symptoms and overall health status in a predominantly Chinese patient population with previously treated aNSCLC. No new safety signals were observed. These findings are similar to the global population.